Children's perceptions of obesity as explained by the common sense model of illness representation - Babooram, M.; Mullan, Barbara; Sharpe, L. (Emerald Group Publishing Limited, 2011)
Purpose – The aim of this paper is to qualitatively examine the ways in which primary school children, aged between 7 and 12, perceive various facets of obesity as defined by the common sense model of illness representation (CCM). Design/methodology/approach – The study was qualitative in nature. Semi-structured interviews were conducted with 33 children on all dimensions of the CSM. Twenty four children were normal weight and nine were overweight. A drawing task formed the methodology for the “identity” section of the interview. Findings – Although children identified food intake as a main cause of obesity, almost half did not name sedentary behaviours as a cause of obesity. Duration (timeline) of obesity was regarded by most children as reliant on a person’s undertaking of positive health behaviours. Normal weight children were found to list more severe consequences of obesity than the overweight group. It was found that experience contributed to the detailed knowledge of overweight children’s perceptions of cures of obesity. Overweight children also spoke of personal incidents of barriers to cures. Practical implications – The findings suggest that the CSMs can be used to classify children’s perceptions of obesity. Future childhood obesity interventions can utilise these findings to create campaigns and strategies that are more consistent with children’s understandings of this condition. Originality/value – To the authors’ knowledge, no previous study has examined children’s perceptions of obesity beyond perceived causes.